A note on taxonomy of the genus Abelmoschus in India with special reference to the vulnerable status of Abelmoschus moschatus subsp. tuberosus (Span) Borá - Velayudhan, K.C.=700 1 Abdul Nizar, M.
(Es, En, Pt)